Historiography Problem Research of Ukrainian Educational Thought Development in the Second Half of XVII – XVIII Century - Kochubei, Tetyana (Pedagogical Discourse, 2013)
Historiographical overview of Ukrainian educational thought development in the second half of the XVII-XVIII centuries is found out, that is based on a systematic study of the philosophical and theological texts and national studies dedicated to this period. The analyzing sources related to various institutions activities, especially the Kyiv Mohyla Academy, and colleges operated at that time on the territory of Ukraine and provided practical implementation of educational thought. Kiev-Mohyla Academy professors’ philosophical views are outlined. Historical and cultural phenomena are considered in the article, the leading role among them belongs to the Baroque main features characteristic, the content and teaching methods, development of Ukrainian publishing as a means of sharing ideas and views.